Cultural discourses in apartheid-era psychology, 1980–1994. (December 2015) - Sher, Daniel; Long, Wahbie
Since the 1970s, "indigenous psychology" has blossomed into a global movement that seeks to tailor psychological knowledge and practices for use in other-than-western contexts. Prompted by the often apolitical presentation of indigenization imperatives in academic discourse, this article critically examines conceptualizations of "culture" in the South African Journal of Psychology and Psychology in Society between 1980 and 1994. In a discourse analysis of 48 journal articles, three cultural discourses are identified. Discourse 1 conceptualizes "culture" on the basis of an essentialist ontology and advocates a position of cultural relativism and Discourse 2 draws on a social constructionist ontology that advances an anti-essentialist position, while Discourse 3 relies on a neo-primordial ontology that favors a pluralist position. By identifying the discursive functions of these formations in relation to the broader South African political context, this article reveals striking parallels between psychological and political cultural discourses.